2021
DOI: 10.1186/s12873-021-00481-9
|View full text |Cite
|
Sign up to set email alerts
|

Does Case Management Provide Support for Staff Facing Frequent Users of Emergency Departments? A Comparative Mixed-Method Evaluation of ED Staff Perception

Abstract: Objective Frequent users of emergency departments (FUED) account for a disproportionate number of emergency department (ED) visits and contribute to a wide range of challenges for ED staff. While several research has documented that case management (CM) tailored to FUED leads to a reduction in ED visits and a better quality of life (QoL) among FUED, whether there is added value for ED staff remains to be explored. This study aimed to compare, among staff in two academic EDs in Switzerland (one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(51 reference statements)
1
3
0
Order By: Relevance
“…The need for FUED to justify their visit to the ED was strong, and some mentioned a feeling of illegitimacy. These findings align with previous research describing the propensity of certain healthcare professionals to consider FUED’s recourse to the ED as illegitimate, 30 even influencing FUED’s access to medications. 31 In another study, most healthcare professionals at our hospital considered the motives provided for the ED visit inappropriate, whereas in most instances patients had in fact consulted for acute needs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The need for FUED to justify their visit to the ED was strong, and some mentioned a feeling of illegitimacy. These findings align with previous research describing the propensity of certain healthcare professionals to consider FUED’s recourse to the ED as illegitimate, 30 even influencing FUED’s access to medications. 31 In another study, most healthcare professionals at our hospital considered the motives provided for the ED visit inappropriate, whereas in most instances patients had in fact consulted for acute needs.…”
Section: Discussionsupporting
confidence: 90%
“… 31 In another study, most healthcare professionals at our hospital considered the motives provided for the ED visit inappropriate, whereas in most instances patients had in fact consulted for acute needs. 30 Furthermore, the healthcare workers’ feelings were reported to be borne out by participants' perceptions. 32 These reports are important to consider, as the perception of being discriminated against is associated with greater vulnerability and worse patient self-assessment of their health.…”
Section: Discussionmentioning
confidence: 99%
“…Grazioli et al proposed a protocol for implementation of case management in the Swiss health care system [ 24 ]. Such protocols will have to be adapted to the different healthcare systems, especially in the current context of overcrowded EDs that are also facing a shortage of doctors and nurses, in France as in other countries [ 25 27 ]. Little is known about the impact of CM on deprived frequent ED users and interventional trials in this population are crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews suggested that case management could reduce ED visits [ 12 , 14 , 29 , 30 ] and be cost-effective [ 31 ], but few specifically targeted vulnerable patients [ 13 , 29 , 30 ]. Case management involves multi-disciplinary teams including physicians, nurses, psychologists, social workers and/or housing and community resource liaisons, who develop tailored care strategies and protocols for patients [ 32 35 ]. Little is known about the impact of case management on deprived FUED, and interventional trials in this population are crucial.…”
Section: Introductionmentioning
confidence: 99%